Sistem Informasi Pemesanan Dan Penjualan Barang pada Pintera Kreativ Berbasis Web - Sembiring, Jocelyne Oktavina; Pakpahan, Sorang (MEANS (Media Informasi Analisa dan Sistem), 2018)
The purpose of this study was to design a web-based and android-based information system at Pintera Kreativ to help increase sales in order to conduct online ordering and to provide product information at Pintera Kreativ through samrtphone or through website pages. The method of research was carried out with two methods namely, method data analysis and information system design. The method of data analysis is carried out in finding the information needed with research and literature studies. Meotde information system design is used in the assessment of problems in data analysis, this method is a database design, making menu structure, making database specifications and making screen displays. The results of the study show that designing an Android-based sales and ordering information system can facilitate Pintera Kreativ in marketing products. and consumers in ordering products by utilizing internet media so that they can work more effectively and efficiently, so that product marketing can develop. The conclusion that can be taken is that the internet is a media in product marketing widely.